School leadership engagement: validation of the Portuguese version of UWES scale - Castro Silva, José; Ferreira, Marco; Pacheco, Patricia; Almeida, Ana (Frontiers in Education, 2023)
The Utrecht Work Engagement Scale (UWES) is a widely used self-report scale with the original twenty-three items and its abbreviated version of nine items to assess workers' engagement. This paper reports a validation study of the UWES-23 17 and UWES-9 using confirmatory factor analysis, its convergent validity and invariance across gender in a sample of 921 Portuguese school leaders. The main findings support a bidimensional conceptualization of work engagement measurement. The Portuguese version of UWES-9 is proposed as a reliable and robust (CFI = .97; TLI = .95; RMSEA = .073) tool to assess work engagement among Portuguese school leadership. The 9-item UWES is a reliable instrument to assess work engagement among Portuguese school leaders and could be used as an effective screening tool in educational contexts.